Development Of An Interactive E-Module Based On The Independent Curriculum In Informatics Learning At Vocational Schools - Stefany, Evy Maya; Ningsih, Puji Rahayu; Diana, Luluk Mauli; Hariri, Naila (EDUTIC, 2025)
This research aims to develop an interactive e-module based on the Independent Curriculum to support Informatics learning in class X, especially in Data Analysis materials. This research is motivated by learning problems at SMKN 1 Kwanyar, where the learning process still depends on PowerPoint media and structured digital learning resources are not available. The research method used is Research and Development (RD) with a 4D development model (Define, Design, Develop, and Disseminate). The e-module product was validated by two experts, namely media experts and material experts, and tested on students through two stages of field tests in the form of a small group trial involving 5 students and a large group trial involving 24 students. The validation results showed an excellent level of eligibility, namely 96.67% of media experts, 92% of material experts, and an average of 91% of student responses. The findings show that the e-modules developed are valid, practical, and effective in using digital learning media. Interactive features, systematic material structure, and web-based accessibility make this e-module suitable to support independent learning and increase student engagement according to the demands of the Independent Curriculum.